Composite gas drying agent as well as preparation method and application thereof

By preparing the composite gas desiccant, using the combination of flash dehydration and FAU-type molecular sieve raw powder, the problem of insufficient water adsorption amount and compressive strength of the existing activated alumina desiccant is solved, and efficient water adsorption and compressive performance are achieved.

CN119588305APending Publication Date: 2025-03-11LUOYANG JALON MICRO NANO NEW MATERIALS CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411896100.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-23
Publication Date
2025-03-11

AI Technical Summary

Technical Problem

The amount of water adsorption and compressive strength of existing activated alumina desiccants still need to be improved.

Method used

By pre-drying, crushing and flash dehydrating aluminum hydroxide, activated alumina powder is obtained, and mixed with FAU-type molecular sieve raw powder and ammonium bicarbonate aqueous solution for molding and health preservation, and finally drying and calculating to prepare a composite gas desiccant.

Benefits of technology

The prepared composite gas desiccant has excellent water adsorption properties, compressive strength and CO2 adsorption properties. The static water adsorption amount is ≥21%, the crushing force is ≥140N, and the specific surface area is ≥395m2/g.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005201902250000081
    Figure BDA0005201902250000081
Patent Text Reader

Abstract

The invention provides a composite gas drying agent as well as a preparation method and application thereof, and relates to the technical field of drying agents. The method comprises the following steps: sequentially carrying out pre-drying, crushing and flash dehydration on aluminum hydroxide to obtain activated aluminum oxide powder; mixing the activated aluminum oxide powder with FAU type molecular sieve raw powder and forming liquid (ammonium bicarbonate aqueous solution), and forming to obtain a to-be-cured intermediate; performing health maintenance on the intermediate to be subjected to health maintenance to obtain a health maintenance intermediate; and sequentially drying and roasting the curing intermediate to obtain the composite gas drying agent. The prepared composite gas drying agent has excellent water adsorption performance and compressive strength, and also has excellent CO2 adsorption performance. The result of the embodiment shows that the static water adsorption (25 DEG C, RH 60%) of the composite gas drying agent is larger than or equal to 21%, the static CO2 adsorption capacity (25 DEG C, 250 mmHg) is larger than or equal to 8%, and the crushing resistance is larger than or equal to 140 N.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of desiccants, and in particular to a composite gas desiccant and a preparation method and application thereof. Background Art

[0002] Desiccant, also called dehydration adsorbent, is used in food, building materials, housing, chemical industry, electronics and other fields for moisture-proof, mildew-proof, dehydration and other aspects. Activated alumina is a commonly used desiccant.

[0003] Activated alumina balls are pure alumina products with rich and developed pores inside that are interconnected. They have large pore volume and specific surface area and are porous, highly dispersed solid materials. Activated alumina has a relatively strong affinity with water, so it has strong hygroscopicity. Alumina has good chemical stability and high strength, so it does not swell or crack after absorbing water, and can perfectly maintain its original state. Therefore, it is widely used as a desiccant for various gases. The current industrial activated alumina standard-HG / T 3927-2020 stipulates that the static water adsorption capacity of Class VI (used as air separation desiccant) industrial activated alumina is ≥17% (generally 17-19% in industry); the crushing resistance of Class VI industrial activated alumina with a particle size of 3.0-5.0mm is ≥120N (generally about 140N in industry). At present, the water adsorption capacity and compressive strength of activated alumina desiccant still need to be improved. Summary of the invention

[0004] In view of this, the object of the present invention is to provide a composite gas desiccant and a preparation method and application thereof. The composite gas desiccant prepared by the present invention has excellent water adsorption performance and compressive strength.

[0005] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:

[0006] The present invention provides a method for preparing a composite gas desiccant, comprising the following steps:

[0007] Pre-drying, crushing and flash dehydrating aluminum hydroxide in sequence to obtain activated alumina powder; the inlet temperature of the flash dehydration is 730-800°C, and the outlet temperature is 410-440°C;

[0008] The activated alumina powder is mixed with FAU type molecular sieve raw powder and a molding liquid to obtain an intermediate to be cured; the molding liquid is an ammonium bicarbonate aqueous solution;

[0009] The intermediate to be cured is cured to obtain a cured intermediate; the curing temperature is 35 to 65° C. and the relative humidity is 40 to 60%;

[0010] The health-preserving intermediate is dried and calcined in sequence to obtain the composite gas desiccant.

[0011] Preferably, the specific surface area of ​​the activated alumina powder is 290 to 320 m 2 / g,D 50 The particle size is 6.5 to 12 μm, and the loss on ignition is 6 to 10 wt%.

[0012] Preferably, the FAU molecular sieve raw powder is a sodium-based FAU molecular sieve raw powder, with a silicon-aluminum ratio of 1.95 to 5.5, and D 50 The particle size is 0.5 to 10 μm, and the silicon-aluminum ratio is calculated as the molar ratio of SiO2 to Al2O3.

[0013] Preferably, the mass of the activated alumina powder is 65-80% of the total mass of the FAU type molecular sieve raw powder and the activated alumina powder, and the masses of the FAU type molecular sieve raw powder and the activated alumina powder are respectively measured by dry weight.

[0014] Preferably, the mass fraction of the aqueous solution of ammonium bicarbonate is 0.5-10%; the particle size of the intermediate to be cured is 0.5-5.0 mm, and the surface dry water content is 21-33wt%.

[0015] Preferably, the health-preserving time is 12 to 36 hours.

[0016] Preferably, the drying temperature is 120-180° C., and the holding time is 2-6 hours; the calcining temperature is 350-450° C., and the holding time is 2-4 hours.

[0017] The present invention provides a composite gas desiccant prepared by the preparation method described in the above technical solution.

[0018] Preferably, the specific surface area of ​​the composite gas desiccant is ≥395m 2 / g, loss on ignition ≤8wt%.

[0019] The present invention provides the use of the composite gas desiccant described in the above technical solution in adsorbing water and / or carbon dioxide.

[0020] The present invention provides a method for preparing a composite gas desiccant, comprising the following steps: pre-drying, crushing and flash dehydrating aluminum hydroxide in sequence to obtain activated alumina powder; mixing the activated alumina powder with FAU type molecular sieve raw powder and molding liquid (ammonium bicarbonate aqueous solution) to obtain an intermediate to be cured; curing the intermediate to be cured to obtain a curing intermediate; the curing temperature is 35 to 65°C and the relative humidity is 40 to 60%; and the curing intermediate is dried and roasted in sequence to obtain the composite gas desiccant. Compared with the prior art, the present invention has the following beneficial effects:

[0021] The present invention adopts a flash dehydration process to prepare activated alumina powder, which can quickly remove the crystal water in aluminum hydroxide powder, convert the aluminum hydroxide powder into alumina powder with a high specific surface area, and at the same time has a high static water adsorption capacity; the present invention adds FAU type molecular sieve raw powder, which itself has a high specific surface area, static water adsorption capacity and excellent static CO2 adsorption capacity; the ammonium bicarbonate added in the molding process of the present invention is dried and decomposed into ammonia, CO2 and water for removal, thereby leaving micropores; the above methods are combined to make the desiccant have a high specific surface area, static water adsorption capacity and CO2 adsorption performance;

[0022] The present invention cures the formed intermediate under certain temperature and humidity conditions, which can promote the conversion of alumina into monohydrated alumina and amorphous gel, that is, promotes the hardening of the intermediate, and after drying and calcining, the desiccant has a higher crushing resistance.

[0023] The present invention provides a composite gas desiccant prepared by the preparation method described in the above technical solution. The composite gas desiccant provided by the present invention has excellent water adsorption performance and compressive strength, and also has excellent CO2 adsorption performance. The results of the embodiment show that the static water adsorption (25°C, RH60%) of the composite gas desiccant provided by the present invention is ≥21%, the static CO2 adsorption capacity (25°C, 250mmHg) is ≥8%, the crushing resistance is ≥140N, and the specific surface area is ≥395m 2 / g. DETAILED DESCRIPTION

[0024] The present invention provides a method for preparing a composite gas desiccant, comprising the following steps:

[0025] Pre-drying, crushing and flash dehydrating aluminum hydroxide in sequence to obtain activated alumina powder; the inlet temperature of the flash dehydration is 730-800°C, and the outlet temperature is 410-440°C;

[0026] The activated alumina powder is mixed with FAU type molecular sieve raw powder and a molding liquid to obtain an intermediate to be cured; the molding liquid is an ammonium bicarbonate aqueous solution;

[0027] The intermediate to be cured is cured to obtain a cured intermediate; the curing temperature is 35 to 65° C. and the relative humidity is 40 to 60%;

[0028] The health-preserving intermediate is dried and calcined in sequence to obtain the composite gas desiccant.

[0029] In the present invention, unless otherwise specified, all raw materials involved are commercially available products.

[0030] The invention pre-dries, crushes and flash-dehydrates aluminum hydroxide in sequence to obtain activated aluminum oxide powder.

[0031] In the present invention, the pre-drying is preferably carried out in a flash dryer, and the pre-drying temperature is preferably 120°C, so as to achieve a moisture content of ≤2% (moisture content tested at 110°C / 2h). In the present invention, the crushing is preferably carried out in a hammer mill, and the crushing is based on the particle size required by the activated alumina powder. In the present invention, the inlet temperature of the flash dehydration is 730-800°C, which can be 730, 735, 740, 750, 760, 770, 780 or 790°C, and the outlet temperature is 410-440°C, which can be 410, 420, 430 or 440°C; the flash dehydration is preferably carried out in a flash dehydration furnace. The crushed powder (i.e., aluminum hydroxide powder) obtained by the crushing is flash dehydrated, and the crystal water therein can be quickly removed, and the aluminum hydroxide powder is converted into activated alumina powder with a high specific surface area (flash dehydration can also be called fast deactivation), which has a high static water adsorption capacity. In the present invention, when the inlet temperature of the flash dehydration is too high, the alumina crystal phase will be changed, affecting the static water adsorption capacity, and at the same time causing the ignition loss to be too low, affecting the subsequent curing effect, thereby causing the desiccant to have low crushing resistance; when the inlet temperature of the flash dehydration is too low, the water in the alumina is not completely removed, resulting in a low specific surface area of ​​the activated alumina powder, affecting the static water adsorption index of the finished product. In the present invention, the activated alumina powder is an amorphous state mainly of ρ type, and the specific surface area of ​​the activated alumina powder is preferably 290 to 320 m 2 / g, more preferably 310 to 315 m 2 / g,D 50 The particle size is preferably 6.5 to 12 μm, more preferably 7 to 10 μm, and the ignition loss is preferably 6 to 10 wt%. In the present invention, the ignition loss of the activated alumina powder is measured at 800°C / 2h.

[0032] After obtaining the activated alumina powder, the present invention mixes the activated alumina powder with FAU type molecular sieve raw powder and molding liquid to form an intermediate to be cured.

[0033] In the present invention, the FAU molecular sieve raw powder is preferably a sodium-based FAU molecular sieve (sodium ion exchange degree ≥ 99.8%, the sodium ion exchange degree is calculated as follows: molar ratio Na + / (Na + +K + )) raw powder, the silicon-aluminum ratio is preferably 1.95 to 5.5, more preferably 2.2 to 2.4, D 50The particle size is preferably 0.5-5 μm, more preferably 2-4.5 μm, and the silicon-aluminum ratio is the molar ratio of SiO2 to Al2O3. In the present invention, the FAU molecular sieve raw powder itself has a high specific surface area and static water adsorption capacity and excellent static CO2 adsorption capacity.

[0034] In the present invention, the mass of the activated alumina powder is preferably 65-80% of the total mass of the FAU type molecular sieve raw powder and the activated alumina powder, and can be 65%, 70%, 73%, 75%, 77% or 80%. The mass of the FAU type molecular sieve raw powder and the activated alumina powder are respectively measured by dry weight. In the present invention, the dry weight of the FAU type molecular sieve raw powder is measured under the condition of 550℃ / 1h, and the dry weight of the activated alumina powder is calculated according to the formula: the mass of the activated alumina powder × (1-loss on ignition). In the present invention, when the proportion of the activated alumina powder is too high, the water absorption of the desiccant will be reduced; when the proportion of the activated alumina powder is too low, the crushing resistance of the desiccant will be reduced, and pulverization may occur during use.

[0035] In the present invention, the molding liquid is an aqueous solution of ammonium bicarbonate, and the mass fraction of the aqueous solution of ammonium bicarbonate is preferably 0.5-10%, more preferably 1-2%; in an embodiment of the present invention, the aqueous solution of ammonium bicarbonate is specifically obtained by adding ammonium bicarbonate to deionized water and stirring at room temperature. In the present invention, the amount of the molding liquid added is based on the surface dry water content of the intermediate to be cured.

[0036] In the present invention, the specific operation of mixing the activated alumina powder with the FAU type molecular sieve raw powder and the molding liquid for molding is preferably: mixing the activated alumina powder with the FAU type molecular sieve raw powder to obtain a mixed powder; in a molding device, adding the mixed powder and the molding liquid at the same time to obtain an intermediate to be cured. In the present invention, the mixing is preferably carried out in a mixer. In an embodiment of the present invention, the molding device is specifically a spherical device, that is, the spherical intermediate to be cured is obtained by molding.

[0037] In the present invention, the particle size of the intermediate to be cured is preferably 0.5-5.0 mm, more preferably 3.0-4.0 mm, and the surface dry water content is preferably 25-33 wt %, more preferably 29-31 %. In the present invention, the surface dry water content of the intermediate to be cured is measured at 110° C. / 2 h.

[0038] After obtaining the intermediate to be cured, the present invention cures the intermediate to be cured to obtain the cured intermediate.

[0039] In the present invention, the curing temperature is 35-65°C, which can be 35, 40, 45, 48, 50, 55, 60 or 65°C, the relative humidity (RH) is 40-60%, which can be 40%, 50%, 55% or 60%, and the time is preferably 12-36h, which can be 20, 24, 28h or 30h; the curing is preferably carried out under constant temperature and humidity and static conditions. In an embodiment of the present invention, the curing is specifically to transfer the intermediate to be cured into a constant temperature and humidity curing room and let it stand for the curing. After the curing, the alumina is converted into monohydrated alumina and amorphous gel, which promotes the hardening of the intermediate to be cured, and obtains a curing intermediate with high hardness.

[0040] After obtaining the health-preserving intermediate, the present invention sequentially dries and roasts the health-preserving intermediate to obtain the composite gas desiccant.

[0041] In the present invention, the drying temperature is preferably 120-180°C, more preferably 125-135°C, and the holding time is preferably 2-6h, more preferably 4-5h. The surface water of the health intermediate is removed by the drying, and ammonium bicarbonate is decomposed into ammonia, CO2 and water to form a pore structure. In the present invention, the calcination temperature is preferably 350-450°C, more preferably 380-410°C, and the holding time is preferably 2-4h, more preferably 2.5-3h. The calcination removes moisture from the pores of alumina and molecular sieves, and the pores are opened after dehydration to make the desiccant have water absorption properties.

[0042] After the calcination is completed, it is preferably cooled naturally to room temperature in a dryer to obtain the composite gas desiccant.

[0043] The present invention provides a composite gas desiccant prepared by the preparation method described in the above technical solution. In the present invention, the specific surface area of ​​the composite gas desiccant is preferably ≥395m 2 / g, and the loss on ignition is preferably ≤8wt%. In the present invention, the loss on ignition of the composite gas desiccant is measured under the condition of 800℃ / 2h. The composite gas desiccant provided by the present invention has excellent water adsorption performance and compressive strength, and also has excellent CO2 adsorption performance. Moreover, the alumina in the composite gas desiccant has the characteristic of not releasing heat after absorbing water. At the same time, the amount of molecular sieve in the composite gas desiccant is relatively small, and the heat release during use is not violent. Therefore, the composite gas desiccant has the characteristics of high static water adsorption performance and high safety performance.

[0044] The present invention provides the use of the composite gas desiccant described in the above technical solution in the adsorption of water and / or carbon dioxide. The present invention has no special requirements for the method of the application, and the application method familiar to those skilled in the art can be used.

[0045] In order to further illustrate the present invention, the composite gas desiccant provided by the present invention and its preparation method and application are described in detail below in conjunction with examples, but they should not be construed as limiting the protection scope of the present invention.

[0046] Example 1

[0047] A composite gas desiccant, the preparation steps are as follows:

[0048] (1) 1000 kg of aluminum hydroxide was dried in a flash dryer at 120° C. and crushed in a hammer mill to obtain crushed powder. The crushed powder was flash dehydrated in a flash dehydration furnace (the inlet temperature of the flash dehydration furnace was 770° C. and the outlet temperature was 410° C.) to obtain activated alumina powder, the loss on ignition of which was 7.0 wt %, D 50 The particle size is 7 μm and the specific surface area is 310 m 2 / g.

[0049] (2) Add 3 kg of ammonium bicarbonate into 200 kg of deionized water and stir at room temperature for 15 minutes to obtain a molding liquid.

[0050] (3) Take 20 kg (dry weight, accounting for 27% of the total mass of the sodium-based FAU molecular sieve powder and alumina powder) of sodium-based FAU molecular sieve powder (silicon-aluminum ratio (SiO2 / Al2O3) is 2.3), D 50 The particle size is 4.2 μm, and 54 kg of activated alumina powder prepared in step (1) (dry weight, accounting for 73% of the total mass of the sodium-based FAU molecular sieve raw powder and alumina powder) are mixed in a mixer to obtain a mixed powder. The mixed powder is added to the ball forming equipment while adding the molding liquid (molding liquid dosage 20 kg) to obtain a curing intermediate with a particle size of 3.0 to 4.0 mm (surface dry water content of 30 wt%).

[0051] (4) 30 kg of the intermediate to be cured was transferred to a constant temperature and humidity curing room with a humidity of RH55% and a temperature of 45°C and allowed to cure for 24 hours to obtain a cured intermediate.

[0052] (5) The curing intermediate is dried at 130° C. for 4 h, then heated to 385° C. for calcination for 3 h, and naturally cooled to room temperature in a dryer after calcination to obtain a composite gas desiccant with a loss on ignition of ≤8 wt %.

[0053] Example 2

[0054] The composite gas desiccant was prepared according to the method of Example 1, except that:

[0055] The inlet temperature of the flash dehydration furnace in step (1) is 735°C, and the ignition loss of the activated alumina powder obtained is 7.5wt%, D 50The particle size is 7 μm and the specific surface area is 315 m 2 / g;

[0056] In step (3), the amount of sodium-based FAU molecular sieve powder added is 20 kg (dry weight, accounting for 23% of the total mass of the sodium-based FAU molecular sieve powder and the activated alumina powder), and the amount of activated alumina powder added is 67 kg (dry weight, accounting for 77% of the total mass of the sodium-based FAU molecular sieve powder and the activated alumina powder);

[0057] The rest is the same as Example 1.

[0058] Example 3

[0059] The composite gas desiccant was prepared according to the method of Example 1, except that:

[0060] In step (4), the temperature of the constant temperature and humidity health-care room is 48° C., the humidity is RH50%, and the health-care time is 28 h;

[0061] In step (5), the drying temperature is 120° C., the drying time is 2 h, the roasting temperature is 400° C., and the roasting time is 2 h;

[0062] The rest is the same as Example 1.

[0063] Comparative Example 1

[0064] The composite gas desiccant was prepared according to the method of Example 1, except that:

[0065] In step (4), the temperature of the constant temperature and humidity health room is 35° C. and the humidity is RH25%;

[0066] The rest is the same as Example 1.

[0067] Comparative Example 2

[0068] The composite gas desiccant was prepared according to the method of Example 1, except that:

[0069] In step (3), the amount of sodium-based FAU molecular sieve powder added is 20 kg (dry weight, accounting for 18% of the total mass of the sodium-based FAU molecular sieve powder and the activated alumina powder), and the amount of activated alumina powder added is 91 kg (dry weight, accounting for 82% of the total mass of the sodium-based FAU molecular sieve powder and the activated alumina powder);

[0070] The rest is the same as Example 1.

[0071] Comparative Example 3

[0072] The composite gas desiccant was prepared according to the method of Example 1, except that:

[0073] In step (1), the inlet temperature of the flash dehydration furnace is 850°C, and the ignition loss of the activated alumina powder obtained is 5.5wt%, D 50 The particle size is 7 μm and the specific surface area is 260 m 2 / g;

[0074] The rest is the same as Example 1.

[0075] Comparative Example 4

[0076] The composite gas desiccant was prepared according to the method of Example 1, except that:

[0077] The molecular sieve powder used in step (3) is a sodium-based LTA molecular sieve powder with a silicon-aluminum ratio (SiO2 / Al2O3) of 2.0;

[0078] The rest is the same as Example 1.

[0079] Comparative Example 5

[0080] The composite gas desiccant was prepared according to the method of Example 1, except that:

[0081] In step (3), no sodium-based FAU molecular sieve powder is added, and 74 kg of activated alumina powder is added (dry weight, accounting for 100% of the total mass of the sodium-based FAU molecular sieve powder and the activated alumina powder);

[0082] The rest is the same as Example 1.

[0083] The composite gas desiccant prepared in the embodiment and the comparative example was tested as follows:

[0084] (1) The static water adsorption capacity (25°C, RH 60%) of the composite gas desiccant prepared in the embodiment and the comparative example was analyzed using a constant temperature and humidity chamber;

[0085] (2) The static carbon dioxide adsorption capacity (25° C., 250 mmHg) of the desiccants prepared in the examples and comparative examples was analyzed using a micrometer adsorption instrument;

[0086] (3) Using an intelligent particle strength tester to analyze the crushing resistance of the desiccants prepared in the examples and comparative examples;

[0087] (4) The specific surface area of ​​the desiccants prepared in the examples and comparative examples was analyzed using a Microscope specific surface analyzer.

[0088] The above test results are listed in Table 1.

[0089] Table 1 Test results of desiccants prepared in Examples and Comparative Examples

[0090]

[0091] The above description is only a preferred embodiment of the present invention and does not limit the present invention in any form. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention, and these improvements and modifications should also be regarded as the protection scope of the present invention.

Claims

1. A method for preparing a composite gas desiccant, characterized in that: The following steps are involved: Pre-drying, crushing and flash dehydrating aluminum hydroxide in sequence to obtain activated alumina powder; the inlet temperature of the flash dehydration is 730-800°C, and the outlet temperature is 410-440°C; The activated alumina powder is mixed with FAU type molecular sieve raw powder and a molding liquid to obtain an intermediate to be cured; the molding liquid is an ammonium bicarbonate aqueous solution; The intermediate to be cured is cured to obtain a cured intermediate; the curing temperature is 35 to 65° C. and the relative humidity is 40 to 60%; The health-preserving intermediate is dried and calcined in sequence to obtain the composite gas desiccant.

2. The preparation method according to claim 1, characterized in that: The specific surface area of ​​the activated alumina powder is 290 to 320 m 2 / g,D 50 The particle size is 6.5 to 12 μm, and the loss on ignition is 6 to 10 wt%.

3. The preparation method according to claim 1, characterized in that: The FAU molecular sieve raw powder is a sodium-based FAU molecular sieve raw powder, with a silicon-aluminum ratio of 1.95 to 5.5, D 50 The particle size is 0.5 to 10 μm, and the silicon-aluminum ratio is calculated as the molar ratio of SiO2 to Al2O3.

4. The preparation method according to any one of claims 1 to 3, characterized in that: The mass of the activated alumina powder is 65-80% of the total mass of the FAU type molecular sieve raw powder and the activated alumina powder, and the masses of the FAU type molecular sieve raw powder and the activated alumina powder are respectively measured by dry weight.

5. The preparation method according to claim 1, characterized in that: The mass fraction of the aqueous solution of ammonium bicarbonate is 0.5-10%; the particle size of the intermediate to be cured is 0.5-5.0 mm, and the surface dry water content is 21-33wt%.

6. The preparation method according to claim 1, characterized in that: The time of health preservation is 12 to 36 hours.

7. The preparation method according to claim 1, characterized in that: The drying temperature is 120-180° C., and the heat preservation time is 2-6 hours; the calcination temperature is 350-450° C., and the heat preservation time is 2-4 hours.

8. The composite gas desiccant prepared by the preparation method according to any one of claims 1 to 7.

9. The composite gas desiccant according to claim 8, characterized in that: The specific surface area of ​​the composite gas desiccant is ≥395m 2 / g, loss on ignition ≤8wt%.

10. Use of the composite gas desiccant according to claim 8 or 9 in adsorbing water and / or carbon dioxide.